Mothers’ Knowledge and Skills as Key Factors in Preventing Stunting in Toddlers: A Case Study in Malingping, Banten - Rokayah, Yayah; Kuswandi, Kadar; Nuraeneu, Yaneu; Husnida, Nintinjri (Gema Lingkungan Kesehatan, 2025)
Stunting in children under five years of age remains a serious public health problem in Indonesia because it affects physical growth, cognitive development, and long-term productivity. This study aims to analyse mothers' knowledge and skills in preventing stunting and the relationship between sociodemographic characteristics and these two aspects in the working area of the Malingping Community Health Centre, Banten. The study used a descriptive-analytical survey design with a cross-sectional approach involving 80 mothers of toddlers selected through purposive sampling. Data were collected using a structured questionnaire and analysed univariately and bivariately using the Chi-square test. The results showed that most mothers did not know the definition of stunting (81.3%), its causes (86.3%), signs (83.8%), or how to prevent it (88.8%). Mothers' skills in prevention were also low, with 78.8% unable to prepare a balanced complementary feeding menu, 73.7% lacking hygiene when preparing food, and 81.2% rarely monitoring their children's growth. Bivariate analysis showed no significant relationship between education and knowledge (p = 0.721), but there was a significant relationship between education and skills (p = 0.039). This study concludes that although mothers' knowledge about stunting is still low, practical skills are more influenced by education level. These findings emphasise the importance of educational interventions that not only increase knowledge but also build mothers' practical skills through community-based approaches and support from health cadres.